This preview shows pages 1–2. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.View Full Document
Unformatted text preview: difference equation y[n] y[n-1] y[n-2] = x[n] (1) Assume that the input for the system is x[n] = [n] and that the initial conditions are y[-1] = y[-2] = 0. What will be the output of the system? & =-+ = ] [ ) ( n n z n x x X ) ( ] [ z X n x u + ) ( ] 1 [ ] [ 1 1 z X z z m k x m n x m m k k u +-= +-+-- -& , ] [ = n p n x n d. Apply the unilateral Z transform to Eq. (1) and use the linearity property, the time-shifting property and the initial condition in order to find Y + (z). e. Find an explicit expression for y[n] by calculating the inverse unilateral z-transform of Y + (z)....
View Full Document
This note was uploaded on 11/07/2009 for the course FOFL 4531 taught by Professor Haiza during the Spring '09 term at Carlos Albizu.
- Spring '09